Collaborative Learning Effect on Improving Students’ Creativity and Critical Thinking in the Independent Curriculum - Haerun Nisa; Muhammad Isnaini; Linda Sekar Utami; Islahudin Islahudin (STAI Hubbulwathan Duri, 2023)
Collaborative learning is a pedagogical approach that encourages students to actively engage in discussions and cooperative work within a classroom setting. The method of learning holds significant importance in the pursuit of educational objectives. The objective of this study is to assess the impact of collaborative approaches on enhancing students' creativity and critical thinking skills. The research employed a descriptive test, a data normality test, and multiple linear regression analysis as the chosen methodological approaches. The researchers employed a data collection method by administering a questionnaire to a sample of 48 students engaged in collaborative learning. The questionnaire was distributed via a Google form. The focus of this study is on collaborative learning (Ŷ) as the dependent variable, whereas the independent factors include creativity ability (X1) and critical thinking (X2). The findings of the data analysis were conducted using multiple linear regression tests. The present study employs descriptive quantitative research methodologies, utilising a data collection instrument consisting of a four-point Likert scale questionnaire. Then, the data analysis used is a linear regression test, statistical test and data normality test. From the results of multiple linear regression analysis that has been done, it is obtained that the variables of creativity (X1) and critical thinking (X2) have a linear effect on the application of collaborative learning (Ŷ). It is also seen that the most influential variable is creativity (X1), with a value of 77.9%. The determination value (R2 ) is 0.796, meaning that 79.6% of the increase in creativity and critical thinking is influenced by the application of collaborative learning. Through the ANOVA test, it is also known that all independent variables simultaneously affect the dependent variable and through the T value hypothesis test, it is proven that all independent variables have a significant effect on the dependent variable. So we conclude that there is an effect of the application of collaborative learning in increasing students' creativity and critical thinking in the independent curriculum, with the total effect of creativity of 77.9% and critical thinking of 27.1%.